2016
DOI: 10.1007/s40475-016-0092-0
|View full text |Cite
|
Sign up to set email alerts
|

Human Brucellosis and Adverse Pregnancy Outcomes

Abstract: Purpose of Review Brucellosis is a neglected, zoonotic disease of nearly worldwide distribution. Despite brucellosis being recognized as a reproductive disease in animals, it has been historically known as a flu-like illness in humans with little or no significant role in maternal or newborn health. This review focuses on what is currently known relative to the epidemiology of brucellosis in human pregnancy as well as new insights of placental immunology. Recent Findings New evidence suggests that maternal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 78 publications
0
35
0
Order By: Relevance
“…Symptoms in infected individuals are non-specific and can include fever, sweats, arthralgia, myalgia, and in complicated cases, miscarriage or spontaneous abortion (1,(33)(34)(35). In this study, an attempt to directly correlate confirmed human brucellosis cases with the consumption of raw milk and products was impossible, which demonstrates a gap in evidence of unavailable data reporting human brucellosis acquired from raw milk consumption.…”
Section: Discussionmentioning
confidence: 83%
“…Symptoms in infected individuals are non-specific and can include fever, sweats, arthralgia, myalgia, and in complicated cases, miscarriage or spontaneous abortion (1,(33)(34)(35). In this study, an attempt to directly correlate confirmed human brucellosis cases with the consumption of raw milk and products was impossible, which demonstrates a gap in evidence of unavailable data reporting human brucellosis acquired from raw milk consumption.…”
Section: Discussionmentioning
confidence: 83%
“…This study describes pathologic changes of the non-gravid uterus, broadens the knowledge of Brucella as a pathogen of the reproductive tract, and suggests that pregnancy is not required to generate tropism. Since infertility is also described in non-pregnant women infected with Brucella spp., it is possible that inflammation of the reproductive tract is a contributing factor [33]. Intratracheal inoculation of the guinea pig offers an intriguing model for the study of the host-pathogen interaction that leads to reproductive disease in addition to providing a reliable means of generating systemic and clinical brucellosis that could be used to evaluate vaccine candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Another theory was that amniotic fluid contains anti-Brucella activity [48]. However, many reports describe apparent increased rates of spontaneous abortion, intrauterine fetal death, and preterm birth in mothers with brucellosis during pregnancy [49]. Recognition and suitable treatment of infection in early course of pregnancy lead to decrease of incidence of spontaneous abortion, intrauterine fetal death, and congenital infection [44,[46][47][48][49].…”
Section: Neonatal Brucellosismentioning
confidence: 99%
“…However, many reports describe apparent increased rates of spontaneous abortion, intrauterine fetal death, and preterm birth in mothers with brucellosis during pregnancy [49]. Recognition and suitable treatment of infection in early course of pregnancy lead to decrease of incidence of spontaneous abortion, intrauterine fetal death, and congenital infection [44,[46][47][48][49]. The clinical manifestations of brucellosis in pregnancy are similar to other infected people and include arthralgia, arthritis, fever, chills, sweating, headache, malaise, nausea, vomiting, lymphadenopathy, hepatosplenomegaly, anorexia and weight loss [1][2][3][45][46][47].…”
Section: Neonatal Brucellosismentioning
confidence: 99%
See 1 more Smart Citation